Relationship between breath isoprene excretion and oxidative stress responses to submaximal exercise - Hori, Amane; Suijo, Kenichi; Ogata, Hisayoshi; Baba, Reizo; Kondo, Takaharu; Hotta, Norio (Japanese Journal of Physical Fitness and Sports Medicine, 2020)
The physiological functions of expiratory isoprene, which is abundantly contained in human breath, are not well known. Recently, breath isoprene has been proposed to be related to oxidative stress, although no direct evidence has been reported. Therefore, the purpose of this study was to investigate the relationship between breath isoprene and oxidative stress status. Ten healthy male subjects performed a 20-min submaximal step-load cycling exercise, the intensity of which corresponded to a 60% peak oxygen uptake after a 10-min rest. Breath isoprene excretion during the exercise was calculated from the product of minute ventilation and isoprene expiratory concentration. To evaluate the oxidative stress, we collected blood samples from the subject’s fingertips before and immediately after the end of the exercise, and then diacron reactive oxygen metabolites (d-ROMs), which is an index of oxidative stress level, and biological antioxidant potential (BAP), which is an index of antioxidant potential, were measured. The breath isoprene concentration at the rest was significantly positively correlated with the ratio from BAP to d-ROMs (BAP/d-ROMs), which is an index of latent antioxidant potential (r = 0.63, P < 0.05). Furthermore, the change in breath isoprene excretion from before to after the exercise was significantly negatively correlated with the change in d-ROMs (r = -0.73, P < 0.05) and positively correlated with the change in BAP/d-ROMs (r = 0.88, P < 0.01). These results suggest that isoprene might play a role in the control of oxidative stress.